Vertebrates : comparative anatomy, function, evolution - Kardong, Kenneth V. (©2009., 2012)
'This one-semester text is designed for an upper-level majors course. Vertebrates features a unique emphasis on function and evolution of vertebrates, complete anatomical detail, and excellent pedagogy. Vertebrate groups are organized phylogenetically, and their systems discussed within such a context. Morphology is foremost, but the author has developed and integrated an understanding of function and evolution into the discussion of anatomy of the various systems.'--Publisher's website.
Introduction -- Origin of Chordates -- The vertebrate Story -- Biological Design -- Life History -- Integument -- Skeletal System: The Skull -- Skeletal System: The Axial Skeleton -- Skeletal System: The Appendicular Skeleton -- The Muscular System -- The Respiratory System -- The Circulatory System -- The Digestive System -- The Urogenital System -- The Endocrine System -- The Nervous System -- Sensory Organs -- Conclusions.
Includes index.
Keywords: Vertebrates -- Anatomy; Vertebrates -- Physiology; Anatomy, Comparative; Vertebrates -- Evolution